Electronic packaging, microelectronics, and interconnection dictionary - Harper, Charles A. (Electronic packaging and interconnection series, 1993)
From circuits and communication systems to all types of electronic subsystems and assemblies, this reference includes concise definitions for more than 6000 terms, acronyms, abbreviations and symbols that are commonly encountered by everyone working in the industry, whatever their expertise